Pemodelan Sistem Dinamis Stratejik Intelijen Dalam Meminimalisasi Ancaman Spionase dan Pencurian Privasi Big Data Di Era Industri 4.0 - Jayantho, Seno; Runturambi, Arthur Josias Simon; Ras, Abdul Rivai; Widiawan, Bondan (UI Scholars Hub, 2020)
Information of technology evolution entered the industrial era 4.0 where all companies or other stakeholders use the system to analyze data to get a clear picture of the behavior of consumers or members. This study aims to examine the possible massive threats of industrial systems 4.0 regarding espionage and theft of the privacy of people or consumers using a dynamic system approach. This study uses qualitative methods and dynamic system modeling that connects variables affecting the threat of espionage and theft of big data privacy in the industrial 4.0 system scheme so that a fundamental solution can be obtained to minimize the threat. This analysis uses a theory that explains the relationship between variables, namely industry 4.0 theory, internet of things (IoT) theory, data theory and big data, and theories about privacy security. The conclusion of this study is to examine the possibility of massive threats from the industrial 4.0 system related to espionage and theft of privacy of people or consumers by using a dynamic system approach. Keywords: Industry 4.0, Espionage, Privacy, Internet Of Thing, System-Dynamic